Preparation of Diamino-Bridged bis(b-Cyclodextrin)s and Their Application as Chiral Stationary Phases in HPLC - Chang, Y.X.; Bai, B.; Du*, L.M.; Jing, X.; Li, C.F.; Fu, Y.L. (Asian Journal of Chemistry, 2013)
Three diamino-bridged bis(b-cyclodextrin)s, namely 1,3-(aminomethyl)-benzylamine-bridged bis(6-amino-6-deoxy-b-cyclodextrin) (1), 4,4-diaminodiphenyl methano-bridged bis(6-amino- 6-deoxy-b-cyclodextrin) (2) and 4,4-ethylenedianiline-bridged bis(6-amino-6-deoxy-b-cyclodextrin) (3), were prepared and used in the novel application as chiral stationary phases (CSPs) in HPLC. Their ability to separate 11 enantiomers was investigated using triethylammonium acetate buffer containing methanol as the mobile phase. All three chiral stationary phases, particularly chiral stationary phase-1 (CSP1), have better enantiomer separation efficiencies than the parent b-cyclodextrin. Therefore, the linker length between two cyclodextrin units is effective to enantioselectivity and the resolution ability decreases with increased linker length, which conforms with the molecular recognition ability.